Driving Scheme Optimization for Electrowetting Displays Based on Contact Angle Hysteresis to Achieve Precise Gray-Scales - Wang, Li; Zhang, Hu; Li, Wei; Li, Jiaxuan; Yi, Zhenyu; Wan, Qiming; Zhang, Jitao; Ma, Pengchang (Frontiers in Physics, 2021)
As a new display technology, electrowetting display (EWD) has many excellent display characteristics, such as paper-like, low power consumption, quick response and full color. These characteristics make EWD devices very suitable for portable devices. However, the gray-scale distortion caused by the contact angle hysteresis of EWDs seriously affects the accuracy of gray-scale display. To improve this phenomenon, the hysteresis curve of an EWD panel was studied according to the motion characteristics of advancing contact angle and receding contact angle of oil in a pixel. Then, a driving scheme for EWDs using alternating current (AC) voltage instead of direct current (DC) voltage was proposed in this paper. And the advantages and disadvantages of the driving scheme at different AC frequencies from 90Hz to 2700Hz were analyzed through experiments. According to the stability of aperture ratio in EWDs, a 470Hz AC driving scheme was determined. Experimental results showed that the aperture ratio distortion of EWDs could be reduced from 35.82% to 5.97%, which significantly improved the display performance of pixel units.